The critical factors that influence the new venture creation by retailers in Kelantan - Nur Syuhaila Mohd Yusof; Nur Zafirah Adilah Roslan; Tan Chor Gee; Muhammad Firdaus Mohamed Kamil (2016)
This study aimed to determine the factors that influence the creation of new businesses by retailers for the retail trade in Kelantan. Framework to explain the creation of new businesses that combines four main perspectives in entrepreneurship that are characteristic of the individual (s) who start a business, an organization that they made, a new business environment, and the process by which new businesses started. Quantitative methods were used to analyse the study and the questionnaire as an instrument, a descriptive analysis and Spearman correlation and multiple correlation test was used to analyse the data. The results showed that the process involved in new ventures is the highest affect to the retailers in Kelantan.